Genetic Diversity and Population Structure of Two Tomato Species from the Galapagos Islands - Pailles, Yveline; Ho, Shwen; Pires, Inês S.; Tester, Mark; Negrão, Sónia; Schmöckel, Sandra M. (Frontiers in Plant Science, 2017)
Endemic flora of the Galapagos Islands has adapted to thrive in harsh environmental conditions. The wild tomato species from the Galapagos Islands, Solanum cheesmaniae and Solanum galapagense, are tolerant to various stresses, and can be crossed with cultivated tomato. However, information about genetic diversity and relationships within and between populations is necessary to use these resources efficiently in plant breeding. In this study, we analyzed 3,974 polymorphic SNP markers, obtained through the genotyping-by-sequencing technique, DArTseq, to elucidate the genetic diversity and population structure of 67 accessions of Galapagos tomatoes (compared to two S. lycopersicum varieties and one S. pimpinellifolium accession). Two clustering methods, Principal Component Analysis (PCA) and STRUCTURE, showed clear distinction between the two species and a subdivision in the S. cheesmaniae group corresponding to geographical origin and age of the islands. High genetic variation among the accessions within each species was suggested by the AMOVA. High diversity in the S. cheesmaniae group and its correlation with the islands of origin were also suggested. This indicates a possible influence of the movement of the islands, from west to east, on the gene flow. Additionally, the absence of S. galapagense populations in the eastern islands points to the species divergence occurring after the eastern islands became isolated. Based on these results, it can be concluded that the population structure of the Galapagos tomatoes collection partially explains the evolutionary history of both species, knowledge that facilitates exploitation of their genetic potential for the identification of novel alleles contributing to stress tolerance.